Strengthening the Character of Qolbu Management-Based Students in the Digital Era - M. Thoyyib M. Thoyyib; Muhammad Aziz (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
Strengthening the character of student is one the efforts made by universities as formal education to change and strengthen the character of students for the better so that they are not easly carried away by negative currents of digitalization. The are various efforts that can be made in strengthening student character, one of wich is by implementing qolbu management. Qolbu management is character education that is carried out by bringing the heart closer to Allah SWT because in essence the heart is source dan reflection of human character. A clean heart will create a good character, while a bad heart will creat a bad character. So that with the implementation of character strengthening based on good herat management, it is hoped that it will make student`s heart more consistent, clean, and help student achieve happines in this world and in the hereafter